Attrition rate among patients of Anorectal Malformations on colostomy: A matter of concern - Parveen Kumar; Sauradeep Dey; Ashvin Damdoo; Shishir Kumar; Vivek Manchanda (EL-Med-Pub, 2024)
Background: Anorectal malformations (ARM) are correctable congenital malformations with good prognosis. Traditionally it is managed by staged procedure, with diversion colostomy, followed by definitive procedure and stoma reversal in the third stage. It is recommended to complete all stages of repair by 6 months of age for better long-term continence. We had fewer patients coming for definitive surgery and stoma reversal than the patients undergoing colostomy for ARM, so we planned this study to find out the attrition rate among patients undergoing stoma for ARM and explore the reasons for the same. Methods: An observational study was conducted in the Pediatric Surgery department of Chacha Nehru Bal Chikitsalaya, New Delhi. All the case records of patients with ARM who underwent diversion stoma at our center from January 2018 to December 2019 were retrieved. Further follow-up case records were retrieved with the same Unique Health Identification Number (UHID). When the definitive surgery/ stoma closure was not found in the hospital records till December 2022, the parents were contacted telephonically to find out if the children had undergone definitive surgery at some other center, were awaiting surgery, or had died. The attrition was calculated as the difference between the number of patients for whom a stoma was done and the number of patients who underwent definitive surgery and stoma closure till the data acquisition. Results: A total of 105 patients were included in the study with male preponderance. Colostomy was done for 73.33% of patients in the neonatal period (77/105). The cloacal malformation was found in 7 (6.67%), rectal atresia in 6 (5.71%), and 9 had congenital pouch colon (8.57%). The age at stoma creation for ARM ranged from 1 day to 9.3 years (mean 0.67 ±1.96 years). Cardiac and renal anomalies were among the major associations. 28 of the neonates (26.67%) had stomal complications. Stomal issues were reported in 32.4%. Mortality was reported in 37 patients (35.24%) including 35 neonates. The attrition rate in our study was found to be 38.24% (26 out of 68). Factors contributing to attrition range from anemia and protracted waiting lists to the anesthesiologist's pursuit of optimal patient stabilization, alongside familial or personal matters faced by caregivers. Conclusion: There was a high attrition rate in operated patients of ARM in whom stoma was constructed. The main reasons for the same were anemia and a long surgical waiting list.